Andalusian credit cooperatives in the twentieth century: origin and consolidation of the sector - Vargas-Machuca Salido, María José (REVESCO. Revista de Estudios Cooperativos, 2017)
The main objective of this work is to analyze the history of Andalusian rural credit banks during the twentieth century. We try to study the development from its origin to the consolidation of the sector in the nineties. The first entities of this kind arise in Andalusia in the early years of this century, somewhat later than they did in other European countries and with less push than in other areas of Spain. Since then, numerous small-scale entities appeared linked to Agricultural Unions or as credit sections of agricultural cooperatives. But they did not acquire the status of credit institution. Since mid-century, the Andalusian sector of rural banks begins to take shape with institutions that remain operational until the end of the century. The study of the early life of these companies is not easy due to the lack of documentation. However, since the 1970s, the information is more complete thanks to the publication of the Statistical Yearbook of Credit Unions and Rural Credit Banks, since 1971. The Statistical Bulletin of the Bank of Spain also begins to include provincial information of the activity of these. Based on these sources, a further study of the activity of the Andalusian rural banks between 1975 and 2000 is performed. Two areas are differentiated in the region (East and West) trying to identify distinguishing characteristics in each zone.
Keywords: rural credit banks; agricultural unions; rural cooperatives; credit institutions; expansion.